Molecular docking and simulation studies of natural compounds of Vitex negundo L. against papain-like protease (PLpro) of SARS CoV-2 (coronavirus) to conquer the pandemic situation in the world. Issue 12 (14th July 2022) - Mitra, Debasis; Verma, Devvret; Mahakur, Bhaswatimayee; Kamboj, Anshul; Srivastava, Rakesh; Gupta, Sugam; Pandey, Ajita; Arora, Bhawna; Pant, Kumud; Panneerselvam, P.; Ghosh, Arabinda; Barik, Durga P.; et al.
Abstract: The severe acute respiratory syndrome coronavirus-2 (SARS CoV-2) is β-coronavirus that is responsible for the pandemic coronavirus disease 2019 (COVID-19) all over the world. The rapid spread of the novel SARS CoV-2 worldwide is raising a significant global public health issue with nearly 61.86 million people infected and 1.4 million deaths. To date, no specific drugs are available for the treatment of COVID-19. The inhibition of proteases essential for the proteolytic treatment of viral polyproteins is a conventional therapeutic strategy for conquering viral infections. In the study, molecular docking approach was used to screen potential drug compounds among the phytochemicals of Vitex negundo L. against COVID-19 infection. Molecular docking analysis showed that oleanolic acid forms a stable complex and other phyto-compounds ursolic acid, 3β-acetoxyolean-12-en-27-oic acid and isovitexin of V. negundo natural compounds form a less-stable complex. When compared with the control the synergistic interaction of these compounds shows inhibitory activity against papain-like protease (PL pro ) of SARS CoV-2 (COVID-19). The molecular dynamics (MD) simulation (50 ns) were performed on the complexes of PL pro and the phyto-compounds viz . oleanolic acid, ursolic acid, 3β-acetoxyolean-12-en-27-oic acid and isovitexin followed by the binding free energy calculations using MM-GBSA and these molecules have stable interactions with PL pro protein binding site. The MD simulation study provides more insight into the functional properties of the protein-ligand complex and suggests that these molecules can be considered as a potential drug molecule against COVID-19. In this pandemic situation, these herbal compounds provide a rich resource to produce new antivirals against COVID-19. Communicated by Ramaswamy H. Sarma Graphical Abstract: UF0001 ( V. negundo plant photo: B. Mahakur, Department of Botany and Biotechnology garden, Ravenshaw University, India)